The relevance of denominationalism in the postmodern era with specific reference to the Baptist Union of Southern Africa - Niemandt, Cornelius Johannes Petrus (Nelus) (University of Pretoria, 2013)
Dissertation (MA(Theol))--University of Pretoria, 2012.